DESIGNING A MASCOT FOR PT. ARTERIA DAYA MULIA CIREBON CITY - Annisa, Tri (Arty: Jurnal Seni Rupa, 2025)
Arteria Daya Mulia is a fishing net manufacturing company established in 1982 in Cirebon. In the face of the challenges of globalization and market competition, companies need more modern visual strategies to strengthen brand identity. This research designs mascots as an effective visual communication medium through the IDEO (Inspiration, ideation, implementation) design thinking model. Mascots are designed to represent the company's core values such as quality, strength, and loyalty, while also increasing employee engagement and brand appeal. Implementation is carried out through merchandise media such as t-shirts, hats and totebags to expand market reach and build the company's image. The results show that appropriately designed mascots are able to increase brand awareness, strengthen visual identity, and become a strategic communication tool between companies and audiences.